UAV - Red Green Blue (RGB) Orthomosaic from Stordalen - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2020)
Near-ground RGB orthomosaics collected from UAV platforms, by means of RGB cameras containing red, green and blue bands. Nominal pixel resolution is 5 cm.
Abisko Scientific Research Station (2020). UAV - Red Green Blue (RGB) Orthomosaic from Stordalen, 2019-08-16 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/U4o8KrPkEiKw5RsfiCJZeEgX
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap